Biological augmentation of rotator cuff repair using bFGF-loaded electrospun poly(lactide-co-glycolide) fibrous membranes - Zhao S; Zhao J; Dong S; Huangfu X; Li B; Yang H; Zhao J; Cui W (International Journal of Nanomedicine, 2014)
Song Zhao,1,* Jingwen Zhao,3,* Shikui Dong,1 Xiaoqiao Huangfu,1 Bin Li,2,3 Huilin Yang,2,3 Jinzhong Zhao,1 Wenguo Cui2,31Department of Arthroscopic Surgery, Shanghai Jiao Tong University Affiliated Sixth People's Hospital, Shanghai, 2Orthopedic Institute, Soochow University, Suzhou, Jiangsu, 3Department of Orthopedics, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People's Republic of China *These authors contributed equally to this work Abstract: Clinically, rotator cuff tear (RCT) is among the most common shoulder pathologies. Despite significant advances in surgical techniques, the re-tear rate after rotator cuff (RC) repair remains high. Insufficient healing capacity is likely the main factor for reconstruction failure. This study reports on a basic fibroblast growth factor (bFGF)-loaded electrospun poly(lactide-co-glycolide) (PLGA) fibrous membrane for repairing RCT. Implantable biodegradable bFGF–PLGA fibrous membranes were successfully fabricated using emulsion electrospinning technology and then characterized and evaluated with in vitro and in vivo cell proliferation assays and repairs of rat chronic RCTs. Emulsion electrospinning fabricated ultrafine fibers with a core-sheath structure which secured the bioactivity of bFGF in a sustained manner for 3 weeks. Histological observations showed that electrospun fibrous membranes have excellent biocompatibility and biodegradability. At 2, 4, and 8 weeks after in vivo RCT repair surgery, electrospun fibrous membranes significantly increased the area of glycosaminoglycan staining at the tendon–bone interface compared with the control group, and bFGF–PLGA significantly improved collagen organization, as measured by birefringence under polarized light at the healing enthesis compared with the control and PLGA groups. Biomechanical testing showed that the electrospun fibrous membrane groups had a greater ultimate load-to-failure and stiffness than the control group at 4 and 8 weeks. The bFGF–PLGA membranes had the highest ultimate load-to-failure, stiffness, and stress of the healing enthesis, and their superiority compared to PLGA alone was significant. These results demonstrated that electrospun fibrous membranes aid in cell attachment and proliferation, as well as accelerating tendon–bone remodeling, and bFGF-loaded PLGA fibrous membranes have a more pronounced effect on tendon–bone healing. Therefore, augmentation using bFGF–PLGA electrospun fibrous membranes is a promising treatment for RCT. Keywords: rotator cuff tear, bFGF, electrospinning, PLGA, rat model